Selecting and Coding Contentious Episodes - Abel Bojar; Swen Hutter; Sophia Hunger (Contentious Episodes in the Age of Austerity: Studying the Dynamics of Government–Challenger Interactions, 2021)
As we laid out in the introductory chapter of our volume, we propose a rather ambitious and innovative empirical strategy to study contentious politics – what we label as Contentious Episode Analysis (CEA). Having situated our approach in the intermediate meso-level between the “narrative approach” and the “epidemiological” approach exemplified by conventional protest event analysis (for reviews, see Hutter 2014; Koopmans and Rucht 2002), we aim to accomplish two tasks simultaneously. On the one hand, we wish to preserve the rich ontology and conceptual breadth of the “narrative approach” by distinguishing between a diverse set of actors, actions, and interactions in our empirical design. On the other hand, we aim to leverage the empirical scope and rigor of the “epidemiological approach” of protest event analysis by building a quantitative, cross-national dataset that allows for a variable-based analysis of the unfolding of interactions in contentious episodes. Therefore, in our efforts to preserve the strength (and avoid the weaknesses) of the two extant approaches, the main aim we set forth is to build a dataset that gives an accurate and fine-grained picture of the dynamics of political conflict condensed to a limited set of variables.
Keywords: 320